Particle Packing Application for Improvement in the Properties of Compressed Stabilized Earth Blocks with Reduced Clay and Silt - Malkanthi, S. N.; Perera, A. A. D. A. J. (Engineering, Technology & Applied Science Research, 2019)
Soil as a building material has been used in different forms such as mud, adobe, rammed earth and bricks. The present study focuses on producing Compressed Stabilized Earth Blocks (CSEBs) giving attention to the particle size distribution in the soil mixture. The literature established that compressive strength significantly depends on clay and silt content and 25% of clay and silt produce optimum results while no attention has been given to the amount of other, larger particles. Soil grading refers to the combination of different-size particles in a soil mixture. The correct selection of sizes in the correct proportion may cause improvements in CSEB properties. This paper explains the application of particle packing technology for the improvement of CSEB properties. The theoretical concepts provide a continuous particle size distribution, and the soil used for the experiments also has a continuous particle size distribution. The soil used in the experiments was subjected to washing to reduce the clay and silt content. Separated clay and silt and large particles of different sizes were added to the mixture to match particle size distribution to the optimization curves as explained in particle packing theories. The experimental results show that the CSEB properties can be significantly improved by modifying particle size distribution to fit the suggested optimization curves. According to the results, the compressive strength improved by more than 50% with different amounts of cement stabilization. Significant improvements in the dry densities and water absorption ratios of blocks were observed with this particle size modification.